2014
DOI: 10.2478/jengeo-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Habitat Types and Soil Physicochemical Properties in the Spread of a Non Native Shrub Lantana Camara in the Doon Valley, Western Himalaya, India

Abstract: Invasive alien species colonize very aggressively and forcefully, menacing native biodiversity. The success of invasive alien plants is due to their opportunistic exploitation of anthropogenic disturbances, the absence of natural enemies, free from herbivory and frequently their allelopathic competition. Invasive species can have a significant impact on development, affecting sustainability of livelihood, food security and essential ecosystem services and dynamics. Lantana camara is a documented weed of worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…; Osunkoya & Perrett ; Simba et al . ; Mandal & Joshi ). Osunkoya and Perrett () reported that L. camara invasion elevated the soil moisture, pH, Ca, total and organic C, as compared to the uninvaded soils; however, the soil Na, Cl, Cu, Fe, S and Mn were present in low levels in the invaded soils, compared to in the uninvaded soils.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Osunkoya & Perrett ; Simba et al . ; Mandal & Joshi ). Osunkoya and Perrett () reported that L. camara invasion elevated the soil moisture, pH, Ca, total and organic C, as compared to the uninvaded soils; however, the soil Na, Cl, Cu, Fe, S and Mn were present in low levels in the invaded soils, compared to in the uninvaded soils.…”
Section: Discussionmentioning
confidence: 99%
“…; Osunkoya & Perrett ; Simba et al . ; Mandal & Joshi ). However, Osunkoya and Perrett () showed that not all soil nutrients are significantly elevated by L. camara invasion; some nutrients, such as sodium, chloride, iron and manganese, were reduced.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In India, a population of 1599 alien plant species belonging to 842 genera in 161 families can be found, which comprises 8.5% of the country’s total vascular flora. (Khuroo et al 2012; Mandal and Joshi 2014). To control the spread of the invasive species, a zonal control for various invasion levels needs to be in place in the targeted areas (Grice et al 2011, Terblanche et al 2016, and Shackleton et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Global Invasive Species Information Network now identifies L. camara among the top ten invasive species in the world (GISIN, 2011). This species leads to the reduction of the diversity of invaded biotopes, the extinction of native species and the deterioration of the physicochemical properties of the soil (Mandal and Joshi, 2014). It encroaches on agricultural land, reduces the carrying capacity of pastures and poses a threat to many crops (Baars and Heystek, 2003).…”
Section: Introductionmentioning
confidence: 99%